Glass fabric reinforced cementitious matrix: Tensile properties and bond performance on masonry substrate. (15th October 2017) - Leone, Marianovella; Aiello, Maria Antonietta; Balsamo, Alberto; Carozzi, Francesca Giulia; Ceroni, Francesca; Corradi, Marco; Gams, Matija; Garbin, Enrico; Gattesco, Natalino; Krajewski, Piotr; Mazzotti, Claudio; Oliveira, Daniel; et al.
Abstract: Fibre-reinforced composite materials have gained an increasing success, mostly for strengthening, retrofitting, and repairing existing structures. However some problems may arise with the use of traditional FRP (Fiber Reinforced Polymer), particularly when the compatibility with the substrate and the reversibility of the intervention are required, as in case of cultural heritage buildings, or specific exposition conditions may compromise the long term effectiveness of the reinforcement, as in presence of high temperature and humidity. Starting from these considerations new composite materials are emerging as a more effective solution in certain fields of application and under specific service conditions; in this context, mortar-based composite systems, consisting of one or more layers of uni- or bi-directional fibre nets embedded in cement/lime-based matrix layers, can be used as reinforcement of both concrete and masonry structures. However, the research work dealing with these emerging materials and their performances when used as a strengthening system for existing structures is still limited. Both experimental and theoretical investigations are needed in order to deliver reliable design methodologies. In this work, a Round Robin Test aimed to the characterization of both bond with the existing substrate and tensile performance of glass fabric (in the form of grids) coupled with inorganic mortar matrices is presented. The investigation was conducted at fifteen laboratories involved in the RILEM Technical Committee 250-CSM (Composites for the Sustainable Strengthening of Masonry). With the aim of studying the bond behaviour between Fabric Reinforced Cementitious Matrix (FRCM) composites and masonry substrate, single and double lap shear tests were carried out on brick-masonry prisms. Results provide useful informations about the mechanical properties, the bond capacity and the failure mechanisms of different commercially available glass FRCM systems. Finally, critical aspects are underlined to address the progress of the research work.